Contribuição relativa do cálcio extracelular e do retículo sarcoplasmático para o desenvolvimento de força de contração cardíaca de jeju, Hoplerythrinus unitaeniatus - Zanon, Jacqueline Aparecida Ratto (2005)
The present study anlyzed the in vivo and in vitro responses of the ventricular myocardium obtained from Hoplerythrinus unitaeniatus acclimated and tested at 25 ºC. The in vivo heart rate (fH bpm) was obtained (ECG recordings at lead DI of the electrocardiography) from electrodes inserted at cardiac region. Recordings of the isometric contraction force (Fc %) and time-dependent parameters (TPT time to peak tension; THR time to half relaxation) were obtainded in vitro from ventricle strips electrically paced in response to changes in stimulation frequency, extracelular Ca2+ and adrenaline concentrations, and ryanodine (blocker of the sarcoplasmic reticulum SR). The species presented resting fH values of 29.3 ± 0.31 bpm. The increase in twitch force following addition of crescent Ca2+ concentrations to the medium evidenced the importance of the extracellular Ca2+ for the heart contraction. Significant changes in the time-dependent parameters after increments in the Ca2+ extracellular concentration were not recorded. The post rest tension was analyzed with and without addition of 10 µM ryanodine to the medium. A significant post rest potentiation was recorded for the control preparations (100 to 168.3 ± 11.44 %). However, this post rest potentiation was inhibited by ryanodine (100 to 108.6 ± 4.7 %). The impact of increases in the imposed contraction frequency caused a decline of Fc, TPT and THR in frequencies ≥ 0.4 Hz. During increases in frequency, the pre-treatment with ryanodine decreased force only at the highest frequency (38 % at 1.2 Hz), while TPT decreased at 0.6 Hz and THR remained constant. The combination of ryanodine and a tonic level of adrenaline (10-9 M) did not prevent the force decline as frequency was increased. Adrenergic stimulation with a high level of adrenaline (10-6 M) after pretreatment with ryanodine caused positive inotropy in a magnitude that ameliorated the negative inotropic effect of ryanodine. In conclusion, H. unitaeniatus seems to present well-developed intracellular stores of activator Ca2+, resembling those of mammals rather than of terrestrial ectothermic vertebrates. As a difference, this species also depends on extracellular sources of Ca2+ which provide more flexibility to modulate the contraction force.